Effect of Trichoderma-enriched organic charcoal in the integrated wood protection strategy. - Javier Ribera; Mónica Gandía; Jose F Marcos; Maria Del Carmen Bas; Siegfried Fink; Francis W M R Schwarze (PLoS ONE)
The gradual elimination of chromium from wood preservative formulations results in higher Cu leaching and increased susceptibility to wood decay fungi. Finding a sustainable strategy in wood protection has become of great interest among researchers. The objective of these in vitro studies was to demonstrate the effect of T-720-enriched organic charcoal (biochar) against five wood decay basidiomycetes isolated from strongly damaged poles. For this purpose, the antagonistic potential of Trichoderma harzianum (strain T-720) was confirmed among other four Trichoderma spp. against five brown-rot basidiomycetes in dual culture tests. T-720 was genetically transformed and tagged with the green fluorescent protein (GFP) in order to study its antagonistic mechanism against wood decay basidiomycetes. It was also demonstrated that T-720 inhibits the oxalic acid production by basidiomycetes, a well-known mechanism used by brown-rot fungi to detoxify Cu from impregnated wood. Additionally, this study evaluated the effect of biochar, alone or in combination with T-720, on Cu leaching by different preservatives, pH stabilization and prevention of wood decay caused by five basidiomycetes. Addition of biochar resulted in a significant Cu binding released from impregnated wood specimens. T-720-enriched biochar showed a significant reduction of wood decay caused by four basidiomycetes. The addition of T-720-enriched biochar to the soil into which utility poles are placed may improve the efficiency of Cr-free wood preservatives.